Evaluation of Water Resources Management in Construction Industry – A Model Study - Prasanna Kumar, D; Satish, A; S. Asadi, S (International Journal of Engineering and Technology, 2018)
Construction projects need to be executed to a prefixed time schedule and with the estimated cost according to the plan among all these before starting the project all we need to see was water resources if the resources are not available we cannot start the project. The research was developed in water resources management the techniques, limitations, the future purpose work the overview of all the methods need to be covered. Business have increased now a days to get the additional advantage to the construction project all we need to do was select the area which have surrounding water supplies, underground water level, occurrence of the rainfall all these conditions need to be considered before the construction of the project. While the construction of the project water treatment plants has to be constructed the water used for the household purpose can be reuse by fallowing the treatment techniques. Ground water recharge techniques also have to be implementing to increase the level. The water resource management gives extra benefit to the project the initial cost of these treatment plants will be more but in the future there will be more benefited. This paper describes and finds issues in the water resource management in construction projects and also taken many options of engineers, project managers, people who are living in the local area, site engineers, and irrigation officers. The gathered information from the questionnaire survey is analyzed in AHP Model and developed the importance of the alternatives derives from the issues. This will be helpful for the employees of construction project managers and also to the people who are wasting more water the techniques need to fallow and how to use them and how to treat them how to save water will be considered.Â
Keywords: Construction Project Management; Water Resources; Resource Management; AHP Model.